Medicinally important terpenoids of Ganoderma lucidum from Uttarakhand, India - Singh, R P; Mishra, K K; Verma, R C; Pachauri, Vinita (Mushroom Research, 2012)
The present investigation is aimed to identify the presence of the ganoderic acids A, C2 and H from the methanolic extract of dried fruiting bodies of indigenous Ganoderma lucidum, performing High Performance Liquid Chromatography. The results showed that retention time for standard Ganoderic acids A, C2 and H were 4.2, 3.9 and 4.4 minutes, respectively. The patterns obtained on HPLC analysis of the methanolic extracts of the fruiting bodies of wild and cultivated isolates of Ganoderma lucidum revealed the presence of all the three medicinally important terpenoids, namely, Ganoderic acid A, C2 and H comparing with their respective standards.